A utilização das ferramentas de marketing on- line: um estudo com os mestrandos em administração das universidades federais brasileiras - Dutra, Cinara do Nascimento (2005)
This thesis presents a study about the use of on- line marketing tools by master s students in Administration programs in public Brazilian universities, emphasizing the importance of such tools for the construction of a relationship between the institutions and those audiences in particular. Through the research, it has been investigated the behavior of the master s students in the Internet , his/her preference in relation to the different available tools and which the attributes of such ones he/she judges more important. The on- line marketing is seen as a group of activities which uses electronic communications to publish and to promote the organization, establishing an interaction with the customer and, this way, satisfying his/her needs in an appropriate way. The adoption of electronic tools for such marketing type offers precision, convenience and speed in the moment of looking for the on- line user's knowledge. In that sense, this research revealed that the master's students already have a contact with the Internet up to six years, demonstrating affinity with the technology. Tools as e- mail and web site are constantly used, pointing to a larger preference; following by the newsletter , discussion groups by e- mail , forum of on- line discussion and chats , respectively. Among the attributes of such tools, considered as very important, one can quote the agility, the information, the trust, the safety, the credibility and functionality. Finally, it is necessary to highlight that the present work is divided into six chapters dealing respectively with: revision of the literature (Technology of the Internet ; Discussion and retrospective of the marketing ; The electronic marketing ; The relationship with the customer); methodological aspects (Formulation of the problem; Delineation of the research; Selection of the sample; Plan, instrument and analysis of data; Limitations of the research); the presentation and analysis of the data; conclusion and the author's contributions and considerations on the accomplished research.